2019
DOI: 10.1016/j.clinthera.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Colchicine in Treating Postoperative and Post-catheter Ablation Atrial Fibrillation

Abstract: AF occurs frequently after cardiac surgery (POAF) and catheter pulmonary vein isolation (postablation AF) and is associated with increased cardiovascular morbidity. A number of trials over the last few years have investigated the role of colchicine in the prevention of POAF and postablation AF targeting the local and systemic inflammatory process that leads to initiation and maintenance of AF. Available data imply that colchicine may have a preventive role in POAF and/or postablation AF. However, certain limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
0
22
0
2
Order By: Relevance
“…Colchicine may also exert anti-fibrotic effects. Clinical trials have demonstrated the potential role of colchicine in reducing the occurrence of atrial fibrillation following catheter ablation and cardiac surgeries [ 50 ]. It has been postulated that the modulation of atrial fibrosis by colchicine is mediated by its effects on interleukin-17 and renin-related pathways [ 51 ].…”
Section: Colchicinementioning
confidence: 99%
“…Colchicine may also exert anti-fibrotic effects. Clinical trials have demonstrated the potential role of colchicine in reducing the occurrence of atrial fibrillation following catheter ablation and cardiac surgeries [ 50 ]. It has been postulated that the modulation of atrial fibrosis by colchicine is mediated by its effects on interleukin-17 and renin-related pathways [ 51 ].…”
Section: Colchicinementioning
confidence: 99%
“…Постоперационная фибрилляция предсердий -частое осложнение кардиоторакальной хирургии, развивающееся у 15-50% пациентов и патогенетически связанное с воспалением [85,86]. В серии исследований и их метаанализе продемонстрирована эффективность колхицина при данной патологии и посткатетерной аблации при фибрилляции предсердий [87].…”
Section: постоперационная фибрилляция предсердийunclassified
“…Preoperative circulating CRP, IL-2, and IL-6 levels have been shown to predict the incidence of POAF ( Maesen et al, 2012 ; Liew et al, 2013 ). Treatment with colchicine, a suppressor of leukocyte activation through inhibition of microtubule formation, may reduce POAF incidence ( Deftereos et al, 2018 ; Vrachatis et al, 2018 ). The COPPS study demonstrated colchicine treatment beginning on postoperative day 3 reduced incidence of POAF ( Imazio et al, 2011 ).…”
Section: Inflammationmentioning
confidence: 99%